Bringing Refutation Texts Back to Their Literacy Roots: What do Critical Literacy and Culturally Responsive Pedagogy Have to Teach us About Students' Conceptual Change?. Issue 1 (November 2022) - Zengilowski, Allison; Nash, Brady L.; Schuetze, Brendan A.; Schallert, Diane L.
Refutation texts are resurfacing as a suggested antidote to misconceptions and "fake news." In a previous critical review of the refutation text literature, we, the author team, suggested further interrogation of the assumptions these texts imply: that learners share the same common misunderstanding about a topic, and that there is one "truth" that should replace the misconception. Building from Hynd's feminist critique of refutation texts, we present in this essay a consideration of how these authoritative and prescriptive texts fit into an educational landscape being transformed by foci on students' autonomy and funds of knowledge. In this position paper, we present the argument that refutation texts and their associated research may conflict with critical literacy perspectives and culturally responsive pedagogies. We examine these three perspectives for how they may view learning and literacy, and conclude the essay by proffering suggestions for future research on refutation text manipulations and for considering how refutational texts might be incorporated in classroom settings that enact culturally responsive pedagogy and critical literacy perspectives.